Cor a 14, the allergenic 2S albumin from hazelnut, is highly thermostable and resistant to gastrointestinal digestion. Issue 10 (6th August 2015) - Pfeifer, Sabine; Bublin, Merima; Dubiela, Pawel; Hummel, Karin; Wortmann, Judith; Hofer, Gerhard; Keller, Walter; Radauer, Christian; Hoffmann‐Sommergruber, Karin
<x xml:space="preserve">Abstract</x> Scope Allergens from nuts frequently induce severe allergic reactions in sensitive individuals. The aim of this study was to elucidate the physicochemical characteristics of natural Cor a 14, the 2S albumin from hazelnut. Methods and results Cor a 14 was purified from raw hazelnuts using a combination of precipitation and chromatographic techniques. The protein was analyzed using gel electrophoresis, MS, and far‐UV circular dichroism (CD) analyses. The immunoglobulin E (IgE) binding of native, heat‐treated, and in vitro digested Cor a 14 was studied. We identified two different Cor a 14 isoforms and showed microclipping at the C‐terminus. CD spectra at room temperature showed the typical characteristics of 2S albumins, and temperatures of more than 80°C were required to start unfolding of Cor a 14 demonstrating its high stability to heat treatment. In vitro digestion experiments revealed that Cor a 14 is resistant to proteolytic degradation. Native and heat‐treated protein was recognized by sera from hazelnut allergic patients. However, denaturation of the allergen led to significantly reduced IgE binding. Conclusion We identified two different isoforms of Cor a 14 displaying high stability under heating and gastric and duodenal conditions. Data from IgE‐binding experiments revealed the existence of both, linear and conformational epitopes.